“The Semantic Implications of the Disjoint Madd (Extended Vowel) in Surah Yusuf: A Descriptive Study.” - .bouchaiba, idriss; brahimi, brahim (El Omda in Linguistics and Discourse Analysis, 2026)
Abstract: The topic of this article is to highlight an aspect of the miraculousness of the Holy Qur’an, which is the miraculousness at the phonemic level in the Qur’an, by showing the effect that the discrete tide has on the words or verses in which it is mentioned. The Qur’an and access to its purposes, and the separate extension is a form of its performance and recitation. In this study, we have tried to clarify the semantic value of the separated extension sound; Where we sought to adapt the tools of the descriptive approach with the analysis procedures, to clarify the semantic relationship between this extension and the verse or word in which it was mentioned, by looking at all its places in a part of the Qur’anic text through Surat Al-Kahf, and thus standing on the extent of the importance of this type of extension in reaching To the mysteries and secrets of this miraculous Holy Book, in its style and organization throughout the ages.